2016
DOI: 10.1186/s12896-016-0311-8
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of lignin and nicotine with white rot fungi for the delignification and detoxification of tobacco stalk

Abstract: BackgroundTobacco stalk is one kind of abundant crop residues in China. The high lignification of tobacco stalk increases its reusing cost and the existing of nicotine will cause serious pollution. The biodegradation of lignocellulosic biomass has been demonstrated to be an environmental and economical approach for the utilization of plant stalk. Meanwhile, many nicotine-degrading microorganisms were found in nature. However, microorganisms which could degraded both nicotine and lignin haven’t been reported. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…White-rot fungi are the most effective bio-degraders of lignocellulosic biomass (e.g., Phanerochaete chrysosporium) and can degrade lignin faster than other microorganisms. Su et al reported that the degradation rate of lignin by Phanerochaete chrysosporium in tobacco stalk was 53.75% in 15 days [33].…”
Section: Lignin Degradation In Soilmentioning
confidence: 99%
“…White-rot fungi are the most effective bio-degraders of lignocellulosic biomass (e.g., Phanerochaete chrysosporium) and can degrade lignin faster than other microorganisms. Su et al reported that the degradation rate of lignin by Phanerochaete chrysosporium in tobacco stalk was 53.75% in 15 days [33].…”
Section: Lignin Degradation In Soilmentioning
confidence: 99%
“…TUFC20056 50% of lignin removal [12] Milled wheat straw Penicillium chrysogenum 27.4% lignin mineralization [54] Milled wheat straw Fusarium oxysporum 23.5% lignin mineralization [54] Milled wheat straw Fusarium solani 22.6% lignin mineralization [54] involved in the fungal attack which decreases methoxy, phenolic, and aliphatic content of lignin. These reactions also cleave aromatic rings, and forms new carbonyl groups [40,41]. Selective type of degradations involves degradation of lignin and hemicellulose compared to cellulose.…”
Section: Fungal Consortiummentioning
confidence: 99%
“…White-rot fungi are identified to grow on woody and herbaceous plants. The most examined white-rot fungi for lignin reduction in a selective way are P. chrysosporium and Phlebia while in a non-selective way Trametes versicolor decrease lignin [10,11,41].…”
Section: Fungal Consortiummentioning
confidence: 99%
See 1 more Smart Citation
“…These processes typically break down large molecules of lignin by applying harsh conditions, such as high temperature, high pressure, and extreme pH 33 while catalysts are usually used. Several classes of microorganisms have been found to possess lignin degradation capabilities, such as white rot fungi, [35][36][37] bacteria, 38,39 and protists. 34 Although the reaction rate and efficiency are high, intensive energy input is typically required.…”
mentioning
confidence: 99%